Memanfaatkan Teknologi Metaverse Berdasarkan Hadits Dan UU NO.1 Tahun 2024 - Yoga Ammar Arifin; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explore the utilization of Metaverse technology within the framework of Hadith teachings and the Indonesian Law No.1 of 2024. Through a qualitative approach and content analysis of relevant texts, this study identifies key intersections between Islamic principles, legal stipulations, and the digital realm. Initial findings suggest that careful application of Metaverse technology can enhance various aspects of life while adhering to Islamic teachings and legal requirements. This study contributes to the ongoing conversation about the role of emerging technologies within religious and legal contexts